Thermal protection composite material and preparation method thereof

The phenolic resin-based thermal protection composite material is prepared by RTM process and drying at room temperature and normal pressure, which solves the problem of insufficient thermal protection performance of phenolic resin-based ablative materials and achieves low-cost and high-efficiency thermal protection effect, which is suitable for thermal protection of supersonic aircraft surfaces.

CN120757814APending Publication Date: 2025-10-10BENGBU LINGKONG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511003240.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-21
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

Existing phenolic resin-based ablative materials have insufficient thermal protection performance, complicated preparation process and high cost.

Method used

The RTM process is used to prepare phenolic resin-based thermal protection composite materials. By drying at room temperature and normal pressure, combined with nanoporous network structure and micron-level flexible reinforcement, a micro-nano multi-level composite protection system is constructed to simplify the preparation process and avoid solvent replacement.

Benefits of technology

A low-density, low-thermal conductivity composite material is prepared with excellent thermal insulation performance, suitable for medium and high density heat flow environments. The material structure has good stability and is suitable for thermal protection of supersonic aircraft surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120757814A_ABST
    Figure CN120757814A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high-temperature thermal protection materials, in particular to a thermal protection composite material and a preparation method thereof. Through an RTM (Resin Transfer Molding) integrated co-gel forming process, a nano porous phenolic aerogel matrix and a microporous flexible quartz fiber felt reinforcement are compounded to prepare the phenolic aerogel composite material with a three-dimensional cross-linked network structure. The preparation process is simple, the cost is low, the density is controllable, the designability is high, and the prepared composite material is suitable for application scenes such as a manned spacecraft reentry atmosphere heat protection system and a hypersonic aircraft pneumatic hot extreme environment component, can effectively resist megawatt transient extreme pneumatic heat flow impact, and has good application prospects. The advantages of light weight, high heat insulation property and low cost are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-temperature heat protection materials, and in particular to a heat protection composite material and a preparation method thereof. Background Art

[0002] When hypersonic vehicles (flying at speeds ≥ Mach 5) fly at high speeds, their noses, leading edges, engine inlets, and other parts experience extreme high temperatures due to intense aerodynamic heating. Under these harsh aerodynamic and thermodynamic coupling conditions, high-performance thermal protection material systems are essential for ensuring the safety and reliability of hypersonic vehicles in service. Because ablative materials can absorb heat through decomposition, vaporization, or phase change in high-temperature environments, they are widely used in hypersonic vehicle thermal protection. Phenolic resin-based ablative materials are currently the primary materials used.

[0003] In their research on phenolic resin-based ablative materials, the inventors discovered that traditional phenolic resin-based ablative materials have problems such as high density, insufficient thermal protection efficiency, or decreased mechanical properties. To address this issue, in recent years, domestic and foreign researchers have conducted a series of studies using sol-gel technology combined with RTM technology to prepare phenolic aerogel-based composite materials. For example, Chinese patent CN112920449A discloses a method for preparing a low-density, high-strength phenolic aerogel material. The drying process is almost free of shrinkage, cracking, and other problems. However, solvent replacement is required before the drying process to reduce surface tension, which increases costs and prolongs the preparation cycle. The large amount of organic solvent replaced can cause environmental pollution. The phenolic aerogel composite material prepared by the sol-gel curing method in Chinese patent CN118725583A requires supercritical drying, which increases manufacturing costs and is not conducive to large-scale production. Summary of the Invention

[0004] In view of this, the purpose of the present invention is to propose a thermal protection composite material and a preparation method thereof, so as to solve the problems in the prior art of insufficient thermal protection performance of phenolic resin-based ablative materials and complicated and high-cost preparation processes.

[0005] Based on the above objectives, the present invention provides a method for preparing a thermal protective composite material, the preparation method comprising the following steps:

[0006] 1) dissolving phenolic resin and curing agent in an organic solvent, and stirring to dissolve to obtain a mixed solution;

[0007] 2) injection molding the mixed solution and then performing a curing reaction to obtain a wet gel composite material;

[0008] 3) The wet gel composite material is sequentially subjected to standing treatment at room temperature and drying treatment at normal pressure to obtain an ablative thermal protection composite material.

[0009] The prepared composite material uses nanoporous network structure phenolic aerogel as the matrix and combines it with micron-level flexible reinforcement to construct a micro-nano multi-level composite protection system.

[0010] As an optional embodiment, the injection molding is a resin transfer molding (RTM) process, which specifically includes the following steps: placing the reinforcing material in the mold, vacuuming the mold, injecting the mixed solution into the mold at a certain rate, and performing degassing after the injection molding is completed.

[0011] As an optional embodiment, the certain rate is 5 to 20 mL / min.

[0012] As an optional implementation manner, the degassing treatment time is 0.5h to 2h.

[0013] As an optional embodiment, the reinforcing material is quartz fiber felt with a density of 0.2 to 0.5 g / cm 3 , thickness 5~16mm.

[0014] As an optional implementation manner, in step 1), the mass ratio of the phenolic resin to the organic solvent is 1 / 15 to 1 / 3; and the mass ratio of the curing agent to the phenolic resin is 1 / 10 to 1 / 4.

[0015] As an optional embodiment, the phenolic resin is a thermoplastic phenolic resin, the curing agent is hexamethylenetetramine, and the organic solvent is at least one of anhydrous ethanol, isopropyl alcohol or ethylene glycol.

[0016] As an optional embodiment, the curing temperature of the curing reaction in step 2) is 70 to 110° C., and the curing time is 12 to 48 hours.

[0017] As an optional embodiment, the drying in step 3) adopts a gradient temperature increase, the temperature is 25 to 100° C., and the drying time is 1 to 3 days.

[0018] A thermal protection composite material is prepared by adopting the preparation method.

[0019] Beneficial effects of the present invention:

[0020] 1. The composite material produced by the present invention is prepared using the RTM process. Drying at room temperature and pressure without solvent replacement yields a low-density, low-thermal-conductivity composite material. This process is simple, the preparation cycle is short, and the resulting composite material exhibits excellent thermal insulation properties. It is suitable for medium- to high-density heat fluxes and medium- to long-duration thermal insulation flight environments.

[0021] 2. The composite material prepared by the present invention has nanoscale pores (10 to 70 nm) and a pore size smaller than the mean free path of air molecules, which can effectively inhibit the movement of gas molecules and reduce gas heat conduction. During the aerodynamic heating process, the phenolic resin undergoes a thermal decomposition reaction (300 to 600°C), and the resulting porous carbon layer has both antioxidant and heat insulation functions and absorbs a large amount of heat, delaying the transfer of heat to the matrix. The use of quartz fiber felt as a structural reinforcement has a melting point of up to 1700°C and can maintain structural integrity at high temperatures, preventing the composite material from cracking or collapsing due to thermal stress. The flexible network structure of the fiber felt can effectively alleviate thermal expansion differences and prevent the material from cracking in extreme cold and heat (such as when an aircraft re-enters the atmosphere). In addition, the micron-scale pores of the quartz fiber felt and the nanoscale pores of the phenolic resin form a "multi-scale pore structure", which further extends the heat transfer path, and has adjustable density, low thermal conductivity, and excellent heat insulation performance.

[0022] 3. In the present invention, since RTM is a closed film process, it can produce parts with complex geometric shapes such as reinforcing ribs, inserts, curved surfaces, etc., with high surface finish and precise dimensions. The molded parts do not require additional processing, so the production of surface heat protection parts can be designed into different shapes according to product requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 This is a SEM image of the composite material prepared in Example 2 of the present invention;

[0025] Figure 2 These are SEM images of the micromorphology of the phenolic aerogel in the composite materials prepared in Examples 1-4 of the present invention, wherein a is Example 1, b is Example 2, c is Example 3, and d is Example 4;

[0026] Figure 3 This is a back-temperature curve of a sample prepared in Example 5 of the present invention under a quartz lamp thermal test at 900°C;

[0027] Figure 4 This is a SEM image of the composite material prepared in Comparative Example 1 of the present invention;

[0028] Figure 5 This is an SEM image of the composite material prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to specific embodiments.

[0030] It should be noted that, unless otherwise defined, the technical or scientific terms used in the present invention should have the usual meanings understood by people with ordinary skills in the field to which the present invention belongs. The "first", "second" and similar words used in the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. "Include" or "comprise" and similar words mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. "Connect" or "connected" and similar words are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the object being described changes, the relative positional relationship may also change accordingly.

[0031] In order to solve the problems of insufficient thermal protection performance of phenolic resin-based ablative materials in the prior art and the complicated and costly preparation process, the present invention provides a thermal protection composite material prepared by the following method, which comprises the following steps:

[0032] 1) dissolving phenolic resin and curing agent in an organic solvent, and stirring to dissolve to obtain a mixed solution;

[0033] 2) injection molding the mixed solution and then performing a curing reaction to obtain a wet gel composite material;

[0034] 3) The wet gel composite material is sequentially subjected to standing treatment at room temperature and drying treatment at normal pressure to obtain an ablative thermal protection composite material.

[0035] Optionally, the injection molding is a resin transfer molding (RTM) process, which specifically includes the following steps: placing the reinforcing material in a mold, vacuuming the mold, injecting the mixed solution into the mold at a certain rate, and performing degassing after the injection molding is completed.

[0036] Optionally, the certain rate is 5 to 20 mL / min.

[0037] Optionally, the degassing treatment time is 0.5h to 2h, preferably 1h to 2h.

[0038] Optionally, the reinforcing material is quartz fiber felt with a density of 0.2 to 0.5 g / cm 3 , preferably 0.2 to 0.3 g / cm 3 , more preferably 0.3 g / cm 3, thickness 5 to 16 mm, preferably 10 mm.

[0039] Optionally, in step 1), the mass ratio of the phenolic resin to the organic solvent is 1 / 15 to 1 / 3, preferably 1 / 10 to 1 / 3; the mass ratio of the curing agent to the phenolic resin is 1 / 10 to 1 / 4, preferably 1 / 7 to 1 / 4.

[0040] Optionally, the phenolic resin is a thermoplastic phenolic resin, the curing agent is hexamethylenetetramine, and the organic solvent is at least one of anhydrous ethanol, isopropyl alcohol or ethylene glycol, preferably anhydrous ethanol.

[0041] Optionally, the curing temperature of the curing reaction in step 2) is 70 to 110° C., preferably 80 to 100° C., and the curing time is 12 to 48 hours, preferably 16 to 32 hours.

[0042] Optionally, the drying in step 3) adopts a gradient temperature increase, the temperature is 25 to 100° C., preferably 25 to 80° C., and the drying time is 1 to 3 days, preferably 2 to 3 days.

[0043] The composite material prepared by the present invention has nanoscale pores (10 to 70 nm) and a pore size smaller than the mean free path of air molecules, which can effectively inhibit the motion of gas molecules and reduce gas heat conduction. During the aerodynamic heating process, the phenolic resin undergoes a thermal decomposition reaction (300 to 600 ° C), and the resulting porous carbon layer has both antioxidant and heat insulation functions and absorbs a large amount of heat, delaying the transfer of heat to the matrix. The use of quartz fiber felt as a structural reinforcement has a melting point of up to 1700 ° C, which can maintain structural integrity at high temperatures and prevent the composite material from cracking or collapsing due to thermal stress. The flexible network structure of the fiber felt can effectively alleviate the thermal expansion difference and avoid the material from cracking in extreme cold and heat (such as aircraft re-entering the atmosphere). In addition, the micron-scale pores of the quartz fiber felt and the nanoscale pores of the phenolic resin form a "multi-scale pore structure", which further extends the heat transfer path, and has adjustable density, low thermal conductivity, and excellent heat insulation performance.

[0044] The present invention uses atmospheric pressure drying technology to simplify the composite material preparation process, avoiding the complex drying steps in traditional methods and eliminating the need for solvent replacement, thereby reducing energy consumption and costs. Furthermore, the present invention uses a gradient temperature drying process, gradually increasing the temperature to evaporate the solvent, avoiding problems such as damage to the gel pore structure and shrinkage and cracking of the material caused by rapid solvent evaporation.

[0045] As a specific embodiment 1 of the present invention, a thermal protection composite material is prepared by the following method, which specifically includes the following steps:

[0046] Thermoplastic phenolic resin and hexamethylenetetramine were weighed in a measured ratio and added to a beaker containing a certain proportion of anhydrous ethanol. The mixture was mechanically stirred at room temperature until completely dissolved, thereby obtaining a phenolic resin sol. The mass ratio of the phenolic resin to anhydrous ethanol was 1:3, and the mass ratio of the hexamethylenetetramine to the phenolic resin was 1:4.

[0047] The density is 0.3g / cm 3 The quartz fiber felt was cut into 100*100*10mm and placed in a stainless steel mold to evacuate. The above sol was injected into the mold at a certain rate. After the injection molding was completed, degassing treatment was carried out for 1 hour. After completion, the mold was sealed and transferred to a 100℃ forced air drying oven. The sol-gel curing reaction was carried out for 32 hours at a certain rate of 5-20mL / min.

[0048] After the curing is completed, the mold is removed, the wet gel composite material is taken out, and dried at room temperature for 24 hours, and then transferred to a forced air drying oven to dry at 50°C for 24 hours and 80°C for 24 hours to obtain a completely dried ablative thermal protection composite material. The density of the obtained composite material is 0.61g / cm 3 , average particle size 34.96nm, room temperature thermal conductivity 0.082W / m·K.

[0049] As a specific embodiment 2 of the present invention, a thermal protection composite material is prepared by the preparation method of embodiment 1, except that:

[0050] The mass ratio of hexamethylenetetramine to phenolic resin is 1:5; the sol-gel curing reaction is 24 hours.

[0051] The density of the composite material obtained is 0.60 g / cm 3 , average particle size 29.64nm, room temperature thermal conductivity 0.081W / m·K. The SEM image of the composite material is shown in Figure 1 As shown in the figure, it can be seen that after the sol-gel curing reaction, the phenolic resin is evenly filled in the quartz fiber skeleton in the form of nanoparticles. The average particle size of the aerogel particles is about 30nm, and the distribution is relatively uniform; the average pore size is 62nm, which is smaller than the mean free path of air molecules, which can effectively inhibit air heat conduction and reduce thermal conductivity.

[0052] As a specific embodiment 3 of the present invention, a thermal protection composite material is prepared by the preparation method of embodiment 1, except that:

[0053] The mass ratio of hexamethylenetetramine to phenolic resin is 1:6; the sol-gel curing reaction is 20 hours.

[0054] The density of the composite material obtained is 0.59 g / cm 3 , average particle size 24.33nm, room temperature thermal conductivity 0.079W / m·K.

[0055] As a specific embodiment 4 of the present invention, a thermal protection composite material is prepared by the preparation method of embodiment 1, except that:

[0056] The mass ratio of hexamethylenetetramine to phenolic resin is 1:7; the sol-gel curing reaction takes 16 hours.

[0057] The density of the composite material obtained is 0.60 g / cm 3 , average particle size 19.94nm, room temperature thermal conductivity 0.077W / m·K.

[0058] The SEM images of the changes in the particle size of the phenolic resin nanoparticles in the composite materials prepared in Examples 1 to 4 are as follows: Figure 2 As shown in the figure, as the curing agent content gradually decreases, the particle size gradually decreases and the particle size distribution becomes more concentrated. At a high curing agent content (1 / 4), particle agglomeration is more obvious, forming a structure similar to a hardened structure. As the curing agent content decreases (1 / 5), the hardening phenomenon weakens, and some agglomeration can be seen in the figure. As the curing agent content further decreases (1 / 6), the agglomeration phenomenon is significantly improved, and the particle distribution is more uniform. When the curing agent content is reduced to (1 / 7), the particle size is reduced to the minimum, and the particle size and pore distribution are uniform.

[0059] As a specific embodiment 5 of the present invention, a thermal protection composite material is prepared by the preparation method of embodiment 2, except that the mass ratio of phenolic resin to anhydrous ethanol is 1:5.

[0060] The density of the composite material obtained is 0.49 g / cm 3 , average particle size 41.23nm, room temperature thermal conductivity 0.056W / m·K.

[0061] Comparing Example 2 and Example 5, as the resin concentration decreases, the density and thermal conductivity of the composite material decrease accordingly. This is mainly because the number of prepolymer molecules in the sol decreases, resulting in fewer nucleation points and more sufficient monomer growth space, ultimately forming larger nanoparticles.

[0062] As a specific embodiment 6 of the present invention, a thermal protection composite material is prepared by the preparation method of embodiment 2, except that the density of the quartz fiber felt is 0.2 g / cm 3 .

[0063] The density of the composite material obtained is 0.51 g / cm 3 , average particle size 30.75nm, room temperature thermal conductivity 0.059W / m·K.

[0064] Comparing Example 2 and Example 6, reducing the density of the quartz fiber felt makes it easier to impregnate with the phenolic sol, and the density of the composite material is greatly reduced, which can be used in a flight environment with low heat flux density. However, it should be considered that reducing the density of the fiber felt will have an adverse effect on the overall structural stability of the material, and may cause local deformation at high temperatures.

[0065] As a specific embodiment 7 of the present invention, a thermal protection composite material was prepared 5 times by the preparation method of embodiment 2.

[0066] Density fluctuation ±0.02g / cm 3 , thermal conductivity fluctuation is ±0.003W / m·K.

[0067] The repeated tests of Example 7 and the performance tests of the prepared composite material indicate that the composite material prepared by the preparation process adopted in the embodiment of the present invention has stable performance.

[0068] As a specific comparative example 1 of the present invention, a thermal protection composite material was prepared by the preparation method of Example 5, except that the degassing time was 10 minutes.

[0069] The density of the composite material obtained is 0.46 g / cm 3 , average particle size 40.88nm, room temperature thermal conductivity 0.053W / m·K.

[0070] As a specific comparative example 2 of the present invention, a thermal protection composite material was prepared by the preparation method of Example 5, except that no room temperature drying treatment was performed after the curing was completed.

[0071] The density of the composite material obtained is 0.48 g / cm 3 , average particle size 42.87nm, room temperature thermal conductivity 0.057W / m·K.

[0072] As a specific comparative example 3 of the present invention, a thermal protection composite material was prepared by the preparation method of Example 5, except that the sol-gel curing reaction was carried out in a forced air drying oven at 90°C.

[0073] The density of the composite material obtained is 0.5 g / cm 3 , average particle size 39.62nm, room temperature thermal conductivity 0.054W / m·K.

[0074] As a specific comparative example 4 of the present invention, a thermal protection composite material was prepared by the preparation method of Example 5, except that the sol-gel curing reaction time was 16 hours.

[0075] The density of the composite material obtained is 0.51 g / cm 3, average particle size 40.28nm, room temperature thermal conductivity 0.056W / m·K.

[0076] Figure 3 This is a back temperature test curve of the sample obtained in Example 5 after thermal testing at 900°C for 300s. The center temperature of the back side of the composite flat plate is only 154°C, and the surface of the flat plate basically maintains an intact morphology and structure, showing relatively excellent thermal insulation performance and dimensional stability.

[0077] Figure 4 The composite flat sheet obtained in Comparative Example 1 exhibits a relatively short degassing time, preventing complete removal of internal bubbles. This results in a dense distribution of pores on the surface of the sample after the same curing and drying process. Therefore, the degassing time should be extended or shortened based on the fiber mat density and resin solution viscosity, maintaining it for at least 30 minutes to ensure complete removal of bubbles and maintain both structural integrity and excellent thermal conductivity of the prepared composite material.

[0078] Figure 5 The composite flat plate obtained in Comparative Example 2 was not allowed to stand at room temperature after demolding. Since the pores of the wet gel were filled with a large amount of ethanol solvent, direct high-temperature drying caused the surface solvent to evaporate rapidly. The evaporation rate of the solvent on the gel surface was much higher than that inside, resulting in a difference in shrinkage rate inside and outside, causing stress concentration, macro cracks or local fractures in the material, and adversely affecting the structural integrity and thermal insulation uniformity of the material.

[0079] Comparing Example 5 with Comparative Example 3, the sol-gel curing reaction temperature was lowered. Lowering the temperature would prolong the transition time from sol to gel, thereby affecting the particle size of the phenolic resin in the composite material, thereby affecting the thermal conductivity of the composite material.

[0080] Comparing Example 5 with Comparative Example 4, when only the sol-gel curing reaction time is changed, the thermal conductivity of the composite material prepared by this process is slightly affected.

[0081] Performance testing:

[0082] Density test is a conventional test method, density = mass / volume;

[0083] The particle size distribution is measured by Ps software, and the particle size data in the scanning electron microscope image is not less than 100;

[0084] Thermal conductivity test is carried out according to the national standard GB / T 10295-2008.

[0085] In summary, the application has the characteristics of simple preparation process, low cost, easy to obtain raw materials, safety and environmental protection, and strong size designability. The prepared sample has excellent heat insulation performance and can be applied to building fireproof insulation layer and lithium battery insulation layer, especially suitable for the field of surface thermal protection layer of supersonic aircraft. Of course, the above description is not a limitation of the application, and the application is not limited to the above implementation cases. Any person skilled in the art can make various modifications and changes to the technical features of the above embodiments or different embodiments under the idea of the application, and the steps can be implemented in any order. There are many other changes of different aspects of the application as described above, and they are not provided in details for the sake of brevity.

[0086] It should be understood by those skilled in the art that the above discussion of any embodiment is only exemplary and is not intended to imply that the scope (including claims) of the application is limited to these examples; the technical features of the above embodiments or different embodiments can also be combined, and the steps can be implemented in any order, and there are many other changes of different aspects of the application as described above. In order to be brief, they are not provided in details.

[0087] The present application is intended to cover all such alternatives, modifications and variations as fall within the broad scope of the appended claims. Accordingly, any omission, modification, equivalent replacement, improvement, etc. made in the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a thermal protective composite material, characterized in that: The preparation method comprises the following steps: 1) dissolving phenolic resin and curing agent in an organic solvent, and stirring to dissolve to obtain a mixed solution; 2) injection molding the mixed solution and then performing a curing reaction to obtain a wet gel composite material; 3) The wet gel composite material is sequentially subjected to standing treatment at room temperature and drying treatment at normal pressure to obtain an ablative thermal protection composite material.

2. The preparation method according to claim 1, characterized in that The injection molding is a resin transfer molding (RTM) process, which specifically includes the following steps: placing the reinforcement material in a mold, vacuuming the mold, injecting the mixed solution into the mold at a certain rate, and performing a degassing treatment after the injection molding is completed.

3. The preparation method according to claim 2, characterized in that The certain rate is 5 to 20 mL / min.

4. The preparation method according to claim 2, characterized in that The degassing treatment time is 0.5h to 2h.

5. The preparation method according to claim 2, characterized in that The reinforcing material is quartz fiber felt with a density of 0.2 to 0.5 g / cm 3 , thickness 5~16mm.

6. The preparation method according to claim 1, characterized in that In the step 1), the mass ratio of the phenolic resin to the organic solvent is 1 / 15 to 1 / 3; the mass ratio of the curing agent to the phenolic resin is 1 / 10 to 1 / 4.

7. The preparation method according to claim 1 or 5, characterized in that The phenolic resin is a thermoplastic phenolic resin, the curing agent is hexamethylenetetramine, and the organic solvent is at least one of anhydrous ethanol, isopropyl alcohol or ethylene glycol.

8. The preparation method according to claim 1, characterized in that The curing temperature of the curing reaction in step 2) is 70 to 110° C., and the curing time is 12 to 48 hours.

9. The preparation method according to claim 1, characterized in that The drying in step 3) is carried out by gradient temperature increase, the temperature is 25 to 100° C., and the drying time is 1 to 3 days.

10. A thermal protection composite material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Normal-pressure drying preparation method of low-density high-strength phenolic resin aerogel with extremely low shrinkage rate

    CN112920449A

  • Aerogel composite material as well as preparation method and application thereof

    CN118725583A